PENGARUH PENGGUNAAN MODEL SNOWBALL THROWING DISERTAI HANDOUT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI SMA N 2 BAYANG KABUPATEN PESISIR SELATAN - Yeni, Tila Endra; Nurhadi, Nurhadi; Nursyahra, Nursyahra (Pendidikan Biologi, 2013)
ABSTRACT           The research was motivated by the result of student learning is still low. Which is the average value of daily test of biology, expecialy in matery of plant cells and animal cells class in semester one in the class XI (eleven)  or senior high school in Bayang is still under complete minimal criteria  established in that school . To solve this problems and to improve the result of student learning,  the teachers must do innovation in the process of student learning, do innovation in the process of student learning. One model that requires involvement of the student is to apply the model of Snowball Throwing accompanied by handout . This study aimed to examine the influence of result of  student learning in the study of biology through the model accompanied Snowball Throwing and handout in the class XI (eleven) of senior high school in  Bayang Kabupaten pesisir selatan for academic Year 2013/2014. This type of research is experimental with population of the student in the class XI (eleven) in senior high school in bayang listed in the school year 2013/2014 as much as 4 (four) class.  For example is in the class XI (eleven) in IA2 as experimen class and IA4 as control class taken using purposive random sampling technique . The study design was a randomized Only Control Group Design . Based on the analysis results obtained average achievement test in the experimental class was 76.23 and the standard deviation of 14.67 , while the average achievement test control class 70.43 and standard deviation 12.72 . After testing with the t-test is obtained price t.count = 1.7576 and t.table t = 1.6608 means t.count > t.table , then the hypothesis in this study with a level of 95 % is accepted . It can be concluded that the use of models of Snowball Throwing and handout have affect the result of student learning of the study of biology in senior high school in the class  XI (eleven) in Bayang Kabupaten Pesisir Selatan in Academic Year 2013/2014.